The Existence of Post Reform Agricultural Extension Institutional - Purwitasari, Devie (Universitas Negeri Semarang, 2019)
The purpose of this study is to analyze the existence of agricultural extension institutions in Central Java Province. The variables used include institutional changes and the impact of institutional changes. The method of data analysis in this study is a descriptive qualitative method with the model of Miles and Huberman with the validity test of triangulation data. The types of data used are primary data from the Agriculture and Plantation Office of Central Java Province, the Office of Environment and Forestry of Central Java Province, the Semarang City Fisheries Office and Farmers in Central Java Province. Retrieval of data through in-depth interviews, document collection, and documentation. The results showed that institutional change was very dynamic since the formation of the institution. Institutional changes occur because of the evolution of laws and their forced nature. Therefore the institution of agricultural extension does not exist. However, so far the community is still getting a good impact from the extension activities because institutional changes do not reduce the performance of extension workers in the community. It's just that extension workers have not been intensive because the numbers are very minimal. This is overcome by the instructor by making a priority when conducting counseling. Tujuan penelitian ini adalah untuk menganalisis eksistensi kelembagaan penyuluhan pertanian di Provinsi Jawa Tengah. Variabel yang digunakan meliputi perubahan kelembagaan dan dampak perubahan kelembagaan. Metode analisis data dalam penelitian ini adalah metode deskriptif kualitatif dengan model Miles dan Huberman dengan uji keabsahan data triangulasi. Jenis data yang digunakan adalah data primer dari Dinas Pertanian dan Perkebunan Provinsi Jawa Tengah, Dinas Lingkungan Hidup dan Kehutanan Provinsi Jawa Tengah, Dinas Perikanan Kota Semarang dan Petani di Provinsi Jawa Tengah. Pengambilan data melalui wawancara mendalam, pengumpulan dokumen, dan dokumentasi. Hasil penelitian menunjukkan bahwa perubahan kelembagaan sangat dinamis sejak dibentuknya kelembagaan. Perubahan kelembagaan terjadi karena evolusi undang-undang dan sifatnya dipaksakan. Oleh karena itu kelembagaan penyuluhan pertanian sudah tidak eksis. Namun, sejauh ini masyarakat masih tetap mendapatkan dampak baik dari kegiatan penyuluhan karena perubahan kelembagaan tidak mengurangi kinerja penyuluh di masyarakat. Hanya saja penyuluh belum intensif karena jumlahnya sangat minim. Hal ini diatasi oleh penyuluh dengan membuat prioritas saat melakukan penyuluhan.